1994
DOI: 10.1113/jphysiol.1994.sp020358
|View full text |Cite
|
Sign up to set email alerts
|

Bleached pigment activates transduction in isolated rods of the salamander retina.

Abstract: 1. We have used suction electrode recording together with rapid steps into Li' solution and 0 5 mM IBMX solution to estimate the rates of the guanylyl phosphodiesterase (PDE) and guanylyl cyclase in isolated rods of the salamander, Ambystoma tigrinum. 2. We show that both the PDE and cyclase velocities are accelerated by steady background light. The steady velocities of both enzymes appear to be saturating functions of background intensity. 3. Bleaching also accelerates both the PDE and cyclase. This effect is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
203
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(223 citation statements)
references
References 46 publications
16
203
4
Order By: Relevance
“…This might not be surprising given that opsin triggers excitation with a 10 6 -10 7 times smaller efficiency than rhodopsin (Cornwall and Fain, 1994) and given that the light intensity threshold for detection of transducin movement after 1 hr of exposure was estimated to be 20 scotopic cd/m 2 , resulting in the bleaching of ϳ0.02% of the rhodopsin content (ϳ10 4 rhodopsin molecules) per second (Sokolov et al, 2002). The restriction of Tr ␣ immunolocalization to the rod outer segments of RPE65 Ϫ/Ϫ retinas excluded the nonspecific mislocalization of proteins in these rods attributable to cytoskeletal disruption.…”
Section: Discussionmentioning
confidence: 99%
“…This might not be surprising given that opsin triggers excitation with a 10 6 -10 7 times smaller efficiency than rhodopsin (Cornwall and Fain, 1994) and given that the light intensity threshold for detection of transducin movement after 1 hr of exposure was estimated to be 20 scotopic cd/m 2 , resulting in the bleaching of ϳ0.02% of the rhodopsin content (ϳ10 4 rhodopsin molecules) per second (Sokolov et al, 2002). The restriction of Tr ␣ immunolocalization to the rod outer segments of RPE65 Ϫ/Ϫ retinas excluded the nonspecific mislocalization of proteins in these rods attributable to cytoskeletal disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Only after many months of deprivation do the rods start to degenerate, leading to a permanent loss of vision and eventual blindness. (30) The connection between vitamin A deprivation and constant light exposure was for a long time unclear and only became apparent when Cornwall and I (31) showed that opsin can activate the visual cascade. Our experiments demonstrated that opsin even without chromophore is noisy, occasionally triggering the activation of transducin (32) and collectively producing an electrical response; these observations were later confirmed by biochemical measurement of opsin activity.…”
Section: Continuous Light Kills By Activating Transductionmentioning
confidence: 99%
“…Mammalian opsin is considerably noisier, though it still takes of the order of 10 4 -10 5 opsin molecules to have the effect of one Rh* per second. (34) But since activation is proportional to the opsin concentration, (31) and since there are so many opsin molecules in the outer segment during vitamin A deprivation, the combined effect of the opsin of the entire cell can produce an activation equivalent to that produced by a nearly saturating steady light. That is, the free opsin stimulates the visual cascade and acts effectively like a continuous background illumination, which we shall call an equivalent background.…”
Section: Continuous Light Kills By Activating Transductionmentioning
confidence: 99%
“…In contrast to the opsin formed during Meta-II decay following the photoactivation or thermal activation of Rho, the free opsin resulting from spontaneous PSB breaking should not be phosphorylated nor arrestin-bound. Opsin exhibits a low level (~10 À6 relative to fully activated Meta-II Rho, Table 1) of basal activity (31,32). The total number of opsin (~10 4 to 10 5 ) correspond to~0.01 to 0.1 Meta-II Rho per rod cell per second.…”
Section: The Physiological Implications Of Free Opsin In Rod Cell Sigmentioning
confidence: 99%